Cooperative work experience among the third and fourth year students of the Baguio Tech High School, Baguio City, Philippines - Bautista, Rosa C. 1907- (1959)
An attempt to launch a work experience program among the third and fourth year students in the Baguio Tech High School in preparation for the requirements of provisions 6 and 7 of the Bureau of Private Schools Circular No.2, s. 1957 entitled "The Secondary Curriculum for Private Schools Under the Revised Philippine Educational Program" was done in this study. One of the conclusions drawn from the analysis of the results of this study was the possibility for high school juniors and seniors to engage in work experiences with the guidance and supervision of high school teachers.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Education, Cooperative